Development of metacognition-based mathematics learning devices with heuristic strategies on sequences and series - Nadita Lerian Rosendra; Y. Yarman; Edwin Musdi; I Made Arnawa (Research and Development in Education (RaDEn), 2025)
The creation of learning tools that aren't expressly designed to help people enhance their problem-solving abilities serves as a model for creating learning tools that do just that. The goal of this research is to develop metacognition-based learning tools that employ heuristic techniques and comprise instructional modules and student workbooks that satisfy reliable, useful, and efficient standards. Enhancing pupils' capacity to resolve mathematical issues is the aim. Students in SMAN 1 Lengayang's grade X, or Phase E, participated in this study. The Ploomp model approach is used in this development research study. Respondent surveys, RPP implementation observation sheets, teaching module and Student Worksheet (LKPD) validation sheets, and test questions requiring mathematical problem-solving were the tools employed in the data collection process. The study's findings demonstrated the high validity of the learning devices created for LKPD and teaching modules, the practicality test analysis demonstrated that the LKPD was useful in the very useful category, and the effectiveness test results demonstrated that the learning devices were useful in the good category.